The Level of Cortisol In the Oral Fluid In Patients with Generalized Periodontitis with Manifestations of Anxiety - Horodnov Є. В. (Actual Dentistry, 2024)
Actuality. The prevalence of periodontal tissue diseases among the adult population of working age from 35 to 55 years is quite high. It has no tendency to decrease, which makes this problem extremely urgent. Psychoemotional attitude to pain, negative experience of previous treatment, and the patient’s dental anxiety prevent visits to the clinic for a long time, which exacerbates inflammation and complicates the treatment of patients with generalized periodontitis with manifestations of anxiety. Purpose. Analyze the level of cortisol in oral fluid in patients with generalized periodontitis, with manifestations of anxiety before and after treatment. Research materials and methods. A study of the cortisol level was conducted in 157 patients with generalized periodontitis with manifestations of anxiety, aged 35–55 years, and the gender composition of patients—men (28.7%) and women (71.3%). Patients are divided into three groups. The examination was carried out before and after treatment. Research results. It was found that the level of cortisol in the oral fluid increases in patients with generalized periodontitis in those groups with an increased or high level of anxiety. Before treatment, a significant increase in cortisol in the oral fluid was found in groups HP-T1 with a moderate level of anxiety and in groups HP-T2 with a high level of anxiety found a significant increase in cortisol in the oral fluid. After the medical and preventive measures, the cortisol levels decreased. In particular, in the 35–44 age group, at 10:00 a.m., the cortisol level decreased from 3.02 ± 1.87 ng/ml to 2.52 ± 1.57 ng/ml. According to Fisher’s test, it is significantly correlated (p ≤ 0.05) with the group results. In the age group of 45–55 years old treatment, the cortisol level was 3.71 ± 1.9 ng/ml. After treatment, it decreased to 2.77 ± 1.5 ng/ml, which also correlates with the results by group (p ≤ 0.05) according to Fisher’s test. The indicators did not change significantly in the control group. Thus, an increase in the level of inflammation of the periodontal tissues in generalized periodontitis and an increase in the level of anxiety increases the cortisol level in saliva. After the treatment, the results in the groups significantly changed, which was statistically significantly (p < 0.05) different from the indicators of the control group. Conclusions. Oral fluid cortisol testing is a convenient, noninvasive method for assessing anxiety levels in patients. Comprehensive treatment and corrective and preventive measures for patients with generalized periodontitis who manifested anxiety brought the cortisol level closer to the reference values.